Linking physical processes to biological responses: Interdisciplinary observational insights into the enhanced biological productivity of the Cape Verde Archipelago - Florian Schütte; Anna Christina Hans; Marco Schulz; Rebecca Hummels; Olivier Assokpa; Peter Brandt; Rainer Kiko; Arne Körtzinger; Björn Fiedler; Tim Fischer; Elizandro Rodrigues; Henk-Jan Hoving; et al. (Progress in Oceanography, 2025)

In the brain of the beholder: bi-stable motion reveals mesoscopic-scale feedback modulation in V1 - Alessandra Pizzuti; Omer Faruk Gulban; Laurentius Renzo Huber; Judith Carolien Peters; Rainer Goebel (Brain Structure and Function, 2025)
Understanding the neural processes underlying conscious perception remains a central goal in neuroscience. Visual illusions, whether static or dynamic, provide an effective ecological paradigm for studying conscious perception, as they induce subjective experiences from constant visual inputs. While previous neuroimaging studies have dissociated perceptual interpretation of visual motion from sensory input within the motion-sensitive area (hMT+) in humans, less is known about the role of the primary visual area (V1) and its relationship to hMT+ during a bistable perception. To address this, we conducted a layer-fMRI study at 7 T with human participants exposed to a bistable motion quartet stimulus. Despite a constant sensory input, the bistable motion quartet elicits switching horizontal and vertical apparent motion percepts likely due to lateral and feedback connections across low and high-level brain regions (feedback processing). As control, we used an “unambiguous” version of the motion quartet, hereafter referred to as “physical” motion stimulus, where horizontal and vertical motion is physically presented as visual stimulus in an alternated fashion (feedforward processing). With the advantage of a sub-millimeter resolution gained at ultra-high magnetic field (7 Tesla), we aimed to unveil the differential laminar modulation of V1 (early visual area) and hMT+ (high-order visual area) during the physical and bistable condition. Our results indicate that: (1) hMT+ functional activity correlates with conscious perception during both physical and ambiguous stimuli with similar strength. There is no evidence of differential laminar profiles in hMT+ between the two experimental conditions. (2) Between inducer squares, V1 shows a significantly reduced functional response to the ambiguous stimulus compared to the physical stimulus, as it primarily reflects feedback signals with diminished feedforward input. Distinct V1 laminar profiles differentiate the two experimental conditions. (3) The temporal dynamics of V1 and hMT+ become more similar during the ambiguous condition. (4) V1 exhibits reduced specificity to horizontal and vertical motion perception during the ambiguous condition at the retinotopic locations corresponding to the perceived motion. Our findings demonstrate that during the ambiguous condition, there is a stronger temporal coupling between hMT+ and V1 due to feedback signals from hMT+ to V1. Such feedback to V1 might be contributing to the stabilization of the vivid perception of directed motion at the face of constant ambiguous stimulation.

Provenance analysis of the Rhenohercynian Basin and its southern collision zone: transition from a Silurian volcanic arc to the Rhenohercynian shelf (Central European Variscides) - Wolfgang Dörr; Joachim Blau; Linda Marko; Petra Petschick; Rainer Petschick; Peter Prinz-Grimm; Janina Schastok; Felicitász Velledits (International Journal of Earth Sciences, 2025)

Are agri-environmental schemes doing their job? Evidence from Biebrza National Park, Poland - Joanna Sucholas; Zsolt Molnár; Łukasz Łuczaj; Rainer Luick; Peter Poschlod (Land Use Policy, 2025)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Potato yield and quality are linked to cover crop and soil microbiome, respectively - Michael Hemkemeyer; Sanja A. Schwalb; Clara Berendonk; Stefan Geisen; Stefanie Heinze; Rainer Georg Joergensen; Rong Li; Peter Lövenich; Wu Xiong; Florian Wichern (Biology and Fertility of Soils, 2024)
Crop-specific cultivation practices including crop rotation, cover cropping, and fertilisation are key measures for sustainable farming, for which soil microorganisms are important components. This study aims at identifying links between agronomic practices, potato yield and quality as well as soil microorganisms. We analysed the roles of cover crops and of the soil prokaryotic, fungal, and protistan communities in a long-term trial, differing in crop rotation, i.e. winter wheat or silage maize as pre-crop, presence and positioning of oil radish within the rotation, and fertilisation, i.e. mineral fertiliser, straw, manure, or slurry. Up to 16% higher yields were observed when oil radish grew directly before potatoes. Losses of potato quality due to infection with Rhizoctonia solani -induced diseases and common scab was 43–63% lower when wheat + oil radish was pre-crop under manure or straw + slurry fertilisation than for maize as pre-crop. This contrast was also reflected by 42% higher fungal abundance and differences in β-diversity of prokaryotes, fungi, and protists. Those amplicon sequence variants, which were found in the treatments with highest potato qualities and differed in their abundances from other treatments, belonged to Firmicutes (2.4% of the sequences) and Mortierellaceae (28%), which both comprise potential antagonists of phytopathogens. Among protists, Lobosa, especially Copromyxa , was 62% more abundant in the high potato quality plots compared to all others, suggesting that specific higher trophic organisms can improve crop performance. Our findings suggest that successful potato cultivation is related (1) to planting of oil radish before potatoes for increasing yield and (2) to fertilisation with manure or straw + slurry for enriching the microbiome with crop-beneficial taxa.

Main soil microbial groups assessed by phospholipid fatty acid analysis of temperate alley agroforestry systems on crop- and grassland - Katharina Giray; Callum Banfield; Hans-Peter Piepho; Rainer Georg Joergensen; Michaela Dippold; Christine Wachendorf (Applied Soil Ecology, 2024)

Quantitative relationships among high-throughput sequencing, cyanobacteria toxigenic genotype abundance and microcystin occurrence in bathing waters - Magdalena Purker; Stefanie Dobrovolny; Michaela Kreuml; Peter Hufnagl; Alexander Indra; Rainer Kurmayer (Science of The Total Environment, 2023)

Particulate organic carbon export fluxes estimates by 234Th238U disequilibrium in the oxygen minimum zone off the Peruvian coast - Wokil Bam; Beat Gasser; Kanchan Maiti; Isabelle Levy; Juan Carlos Miquel; Roberta L. Hansman; Jan Scholten; Ruifang C. Xie; Stefan Sommer; Rainer Kiko; Peter W. Swarzenski (Marine Chemistry, 2023)

Post-spawning growth acceleration in fish as a result of reduced live weight and thus, increased food conversion efficiency - Daniel Pauly; Rainer Froese; Cui Liang; Johannes Müller; Peter Sorensen (Environmental Biology of Fishes, 2023)

Recombinase polymerase amplification in combination with electrochemical readout for sensitive and specific detection of PIK3CA point mutations - Vanessa Thoeny; Eva Melnik; Melanie Huetter; Malahat Asadi; Pooyan Mehrabi; Thomas Schalkhammer; Walter Pulverer; Thomas Maier; Giorgio C. Mutinati; Peter Lieberzeit; Rainer Hainberger (Analytica Chimica Acta, 2023)

Serratiochelin D, a new siderophore from Serratia marcescens - Peter M. Eze; Viktor E. Simons; Marian Frank; Lasse van Geelen; Chika C. Abba; Sherif S. Ebada; Charles O. Esimone; Festus B.C. Okoye; Peter Proksch; Rainer Kalscheuer (Phytochemistry Letters, 2023)

Two new metabolites from a marine-derived fungus Penicillium ochrochloron - Peter M. Eze; Yang Liu; Viktor E. Simons; Sherif S. Ebada; Tibor Kurtán; Sándor Balázs Király; Charles O. Esimone; Festus B.C. Okoye; Peter Proksch; Rainer Kalscheuer (Phytochemistry Letters, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Chronic ozone exposure impairs the mineral nutrition of date palm (Phoenix dactylifera) seedlings - Leila Arab; Yasutomo Hoshika; Elena Paoletti; Philip J. White; Michael Dannenmann; Heike Mueller; Peter Ache; Rainer Hedrich; Saleh Alfarraj; Ghada Albasher; Heinz Rennenberg (Science of The Total Environment, 2023)

Development of transgenic composite Stylosanthes plants to study root growth regulated by a β-expansin gene, SgEXPB1, under phosphorus deficiency - Linjie Wang; Wenqiang Wang; Ye Miao; Michael Peters; Rainer Schultze-Kraft; Guodao Liu; Zhijian Chen (Plant Cell Reports, 2023)

Carboniferous mafic-ultramafic intrusions in the Eastern Pontides (Pulur Complex): Implications for the source of coeval voluminous granites - Gültekin Topuz; Rainer Altherr; Osman Candan; Jia-Min Wang; Aral I. Okay; Fu-Yuan Wu; Ali Ergen; Thomas Zack; Wolfgang Siebel; Cosmas K. Shangh; Winfried H. Schwarz; Hans-Peter Meyer; et al. (Lithos, 2023)

Paracrine Factors Released by Stem Cells of Mesenchymal Origin and their Effects in Cardiovascular Disease: A Systematic Review of Pre-clinical Studies - Nishani S. Mabotuwana; Lavinia Rech; Joyce Lim; Sean A. Hardy; Lucy A. Murtha; Peter P. Rainer; Andrew J. Boyle (Stem Cell Reviews and Reports, 2022)
Mesenchymal stem cell (MSC) therapy has gained significant traction in the context of cardiovascular repair, and have been proposed to exert their regenerative effects via the secretion of paracrine factors. In this systematic review, we examined the literature and consolidated available evidence for the “paracrine hypothesis”. Two Ovid SP databases were searched using a strategy encompassing paracrine mediated MSC therapy in the context of ischemic heart disease. This yielded 86 articles which met the selection criteria for inclusion in this study. We found that the MSCs utilized in these articles were primarily derived from bone marrow, cardiac tissue, and adipose tissue. We identified 234 individual protective factors across these studies, including VEGF, HGF, and FGF2; which are proposed to exert their effects in a paracrine manner. The data collated in this systematic review identifies secreted paracrine factors that could decrease apoptosis, and increase angiogenesis, cell proliferation, and cell viability. These included studies have also demonstrated that the administration of MSCs and indirectly, their secreted factors can reduce infarct size, and improve left ventricular ejection fraction, contractility, compliance, and vessel density. Furthering our understanding of the way these factors mediate repair could lead to the identification of therapeutic targets for cardiac regeneration. Graphical abstract

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The Photophysiological Response of Nitrogen-Limited Phytoplankton to Episodic Nitrogen Supply Associated With Tropical Instability Waves in the Equatorial Atlantic - Jonathan Sherman; Ajit Subramaniam; Maxim Y. Gorbunov; Ana Fernández-Carrera; Rainer Kiko; Peter Brandt; Paul G. Falkowski (Frontiers in Marine Science, 2022)
In the Equatorial Atlantic nitrogen availability is assumed to control phytoplankton dynamics. However, in situ measurements of phytoplankton physiology and productivity are surprisingly sparse in comparison with the North Atlantic. In addition to the formation of the Equatorial cold tongue in the boreal summer, tropical instability waves (TIWs) and related short-term processes may locally cause episodic events of enhanced nutrient supply to the euphotic layer. Here, we assess changes in phytoplankton photophysiology in response to such episodic events as well as short-term nutrient addition experiments using a pair of custom-built fluorometers that measure chlorophyll a (Chl a ) variable fluorescence and fluorescence lifetimes. The fluorometers were deployed during a transatlantic cruise along the Equator in the fall of 2019. We hypothesized that the Equatorial Atlantic is nitrogen-limited, with an increasing degree of limitation to the west where the cold tongue is not prominent, and that infrequent nitrate injection by TIW related processes are the primary source alleviating this limitation. We further hypothesized phytoplankton are well acclimated to the low levels of nitrogen, and once nitrogen is supplied, they can rapidly utilize it to stimulate growth and productivity. Across three TIW events encountered, we observed increased productivity and chlorophyll a concentration concurrent with a decreased photochemical conversion efficiency and overall photophysiological competency. Moreover, the observed decrease in photosynthetic turnover rates toward the western section suggested a 70% decrease in growth rates compared to their maximum values under nutrient-replete conditions. This decrease aligned with the increased growth rates observed following 24 h incubation with added nitrate in the western section. These results support our hypotheses that nitrogen is the limiting factor in the region and that phytoplankton are in a state of balanced growth, waiting to “body surf” waves of nutrients which fuel growth and productivity.

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Protein expression plasticity contributes to heat and drought tolerance of date palm - Andrea Ghirardo; Tetyana Nosenko; Jürgen Kreuzwieser; J. Barbro Winkler; Jörg Kruse; Andreas Albert; Juliane Merl-Pham; Thomas Lux; Peter Ache; Ina Zimmer; Saleh Alfarraj; Klaus F. X. Mayer; et al. (Oecologia, 2021)
Climate change is increasing the frequency and intensity of warming and drought periods around the globe, currently representing a threat to many plant species. Understanding the resistance and resilience of plants to climate change is, therefore, urgently needed. As date palm ( Phoenix dactylifera) evolved adaptation mechanisms to a xeric environment and can tolerate large diurnal and seasonal temperature fluctuations, we studied the protein expression changes in leaves, volatile organic compound emissions, and photosynthesis in response to variable growth temperatures and soil water deprivation. Plants were grown under controlled environmental conditions of simulated Saudi Arabian summer and winter climates challenged with drought stress. We show that date palm is able to counteract the harsh conditions of the Arabian Peninsula by adjusting the abundances of proteins related to the photosynthetic machinery, abiotic stress and secondary metabolism. Under summer climate and water deprivation, these adjustments included efficient protein expression response mediated by heat shock proteins and the antioxidant system to counteract reactive oxygen species formation. Proteins related to secondary metabolism were downregulated, except for the P. dactylifera isoprene synthase (PdIspS), which was strongly upregulated in response to summer climate and drought. This study reports, for the first time, the identification and functional characterization of the gene encoding for PdIspS, allowing future analysis of isoprene functions in date palm under extreme environments. Overall, the current study shows that reprogramming of the leaf protein profiles confers the date palm heat- and drought tolerance. We conclude that the protein plasticity of date palm is an important mechanism of molecular adaptation to environmental fluctuations.

Analysis of cognitive abilities measured in a laboratory-controlled 360° simulation in soccer - Florian Heilmann; Peter Weigel; Rainer Wollny (German Journal of Exercise and Sport Research, 2021)
Soccer, which is characterized by a very high pace and a short possession time, requires players who are well trained in cognitive abilities. The aim of the study was to quantify cognitive abilities and the improvements in cognitive measures in a laboratory-controlled 360° simulation setting. In all, 82 male youth soccer players (4 age groups) were examined with a pre-/posttest design with an e‑training intervention in a unique 360° simulation tool (SoccerBot360 [Umbrella Software Development GmbH, Leipzig, Germany]). The cognitive abilities, especially executive functions, were measured using cognitive tests (Stroop number test, Corsi Block test, Anticipation tests, Choice Reaction test) modified for the 360° simulation to evaluate executive functions and anticipation. The analyzed soccer players showed significant positive changes in cognitive tests from pre- to posttest and significant group effects. The changes in the cognitive test values are not exclusively due to the additional training in the simulation. Nevertheless, the results show significant differences between the four age groups in cognitive abilities and their development.

Wildlife conservation in a fragmented landscape: the Eurasian red squirrel on the Isle of Wight - Emilie A. Hardouin; Helen Butler; Marin Cvitanović; Rainer G. Ulrich; Vanessa Schulze; Anna-Katarina Schilling; Peter W. W. Lurz; Anna Meredith; Kathy H. Hodder (Conservation Genetics, 2021)
Island populations may have a higher extinction risk due to reduced genetic diversity and need to be managed effectively in order to reduce the risk of biodiversity loss. The Eurasian red squirrels ( Sciurus vulgaris ) in the south of England only survive on three islands (the Isle of Wight, Brownsea and Furzey islands), with the Isle of Wight harbouring the largest population in the region. Fourteen microsatellites were used to determine the genetic structure of red squirrel populations on the Isle of Wight, as well as their relatedness to other populations of the species. Our results demonstrated that squirrels on these islands were less genetically diverse than those in Continental mainland populations, as would be expected. It also confirmed previous results from mitochondrial DNA which indicated that the squirrels on the Isle of Wight were relatively closely related to Brownsea island squirrels in the south of England. Importantly, our findings showed that genetic mixing between squirrels in the east and west of the Isle of Wight was very limited. Given the potential deleterious effects of small population size on genetic health, landscape management to encourage dispersal of squirrels between these populations should be a priority.

Dithiodiketopiperazine derivatives from endophytic fungi Trichoderma harzianum and Epicoccum nigrum - Harwoko Harwoko; Georgios Daletos; Fabian Stuhldreier; Jungho Lee; Sebastian Wesselborg; Michael Feldbrügge; Werner E. G. Müller; Rainer Kalscheuer; Elena Ancheeva; Peter Proksch (Natural Product Research, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Life cycle impact assessment of microplastics as one component of marine plastic debris - Peter Saling; Lora Gyuzeleva; Klaus Wittstock; Victoria Wessolowski; Rainer Griesshammer (The International Journal of Life Cycle Assessment, 2020)

Zooplankton-Mediated Fluxes in the Eastern Tropical North Atlantic - Rainer Kiko; Peter Brandt; Svenja Christiansen; Jannik Faustmann; Iris Kriest; Elizandro Rodrigues; Florian Schütte; Helena Hauss (Frontiers in Marine Science, 2020)

Effects of converting a temperate short-rotation coppice to a silvo-arable alley cropping agroforestry system on soil quality indicators - René Beuschel; Hans-Peter Piepho; Rainer Georg Joergensen; Christine Wachendorf (Agroforestry Systems, 2020)

Aggregated aluminium exposure: risk assessment for the general population - Thomas Tietz; Ariane Lenzner; Anna Elena Kolbaum; Sebastian Zellmer; Christian Riebeling; Rainer Gürtler; Christian Jung; Oliver Kappenstein; Jutta Tentschert; Michael Giulbudagian; Stefan Merkel; Ralph Pirow; et al. (Archives of Toxicology, 2019)
Aluminium is one of the most abundant elements in earth’s crust and its manifold uses result in an exposure of the population from many sources. Developmental toxicity, effects on the urinary tract and neurotoxicity are known effects of aluminium and its compounds. Here, we assessed the health risks resulting from total consumer exposure towards aluminium and various aluminium compounds, including contributions from foodstuffs, food additives, food contact materials (FCM), and cosmetic products. For the estimation of aluminium contents in foodstuff, data from the German “Pilot-Total-Diet-Study” were used, which was conducted as part of the European TDS-Exposure project. These were combined with consumption data from the German National Consumption Survey II to yield aluminium exposure via food for adults. It was found that the average weekly aluminium exposure resulting from food intake amounts to approx. 50% of the tolerable weekly intake (TWI) of 1 mg/kg body weight (bw)/week, derived by the European Food Safety Authority (EFSA). For children, data from the French “Infant Total Diet Study” and the “Second French Total Diet Study” were used to estimate aluminium exposure via food. As a result, the TWI can be exhausted or slightly exceeded—particularly for infants who are not exclusively breastfed and young children relying on specially adapted diets (e.g. soy-based, lactose free, hypoallergenic). When taking into account the overall aluminium exposure from foods, cosmetic products (cosmetics), pharmaceuticals and FCM from uncoated aluminium, a significant exceedance of the EFSA-derived TWI and even the PTWI of 2 mg/kg bw/week, derived by the Joint FAO/WHO Expert Committee on Food Additives, may occur. Specifically, high exposure levels were found for adolescents aged 11–14 years. Although exposure data were collected with special regard to the German population, it is also representative for European and comparable to international consumers. From a toxicological point of view, regular exceedance of the lifetime tolerable aluminium intake (TWI/PTWI) is undesirable, since this results in an increased risk for health impairments. Consequently, recommendations on how to reduce overall aluminium exposure are given.

The Pelagic In situ Observation System (PELAGIOS) to reveal biodiversity, behavior, and ecology of elusive oceanic fauna - Henk-Jan Hoving; Svenja Christiansen; Eduard Fabrizius; Helena Hauss; Rainer Kiko; Peter Linke; Philipp Neitzel; Uwe Piatkowski; Arne Körtzinger (Ocean Science, 2019)
There is a need for cost-efficient tools to explore deep-ocean ecosystems to collect baseline biological observations on pelagic fauna (zooplankton and nekton) and establish the vertical ecological zonation in the deep sea. The Pelagic In situ Observation System (PELAGIOS) is a 3000 m rated slowly (0.5 m s−1) towed camera system with LED illumination, an integrated oceanographic sensor set (CTD-O2) and telemetry allowing for online data acquisition and video inspection (low definition). The high-definition video is stored on the camera and later annotated using software and related to concomitantly recorded environmental data. The PELAGIOS is particularly suitable for open-ocean observations of gelatinous fauna, which is notoriously under-sampled by nets and/or destroyed by fixatives. In addition to counts, diversity, and distribution data as a function of depth and environmental conditions (T, S, O2), in situ observations of behavior, orientation, and species interactions are collected. Here, we present an overview of the technical setup of the PELAGIOS as well as example observations and analyses from the eastern tropical North Atlantic. Comparisons to data from the Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) net sampling and data from the Underwater Vision Profiler (UVP) are provided and discussed.

Cold‐adapted Bacilli isolated from the Qinghai–Tibetan Plateau are able to promote plant growth in extreme environments - Huijun Wu; Qin Gu; Yongli Xie; Zhiying Lou; Pengqi Xue; Liu Fang; Chenjie Yu; Dandan Jia; Guochao Huang; Bichun Zhu; Andy Schneider; Jochen Blom; et al. (Environmental Microbiology, 2019)
Summary Nearly 1400 Bacillus strains growing in the plant rhizosphere were sampled from different sites on the Qinghai–Tibetan Plateau. Forty‐five of the isolates, selected due to their biocontrol activity, were genome‐sequenced and their taxonomic identification revealed that they were representatives of the Bacillus subtilis species complex (20) and the Bacillus cereus group (9). Majority of the remaining strains were found closely related to Bacillus pumilus , but their average nucleotide identity based on BLAST and electronic DNA/DNA hybridization values excluded closer taxonomic identification. A total of 45 different gene clusters involved in synthesis of secondary metabolites were detected by mining the genomes of the 45 selected strains. Except eight mesophilic strains, the 37 remaining strains were found either cold‐adapted or psychrophilic, able to propagate at 10°C and below ( Bacillus wiedmannii NMSL88 and Bacillus sp. RJGP41). Pot experiments performed at 10°C with winter wheat seedlings revealed that cold‐adapted representatives of B. pumilus , B. safensis and B. atrophaeus promoted growth of the seedlings under cold conditions, suggesting that these bacilli isolated from a cold environment are promising candidates for developing of bioformulations useful for application in sustainable agriculture under environmental conditions unfavourable for the mesophilic bacteria presently in use.

A new depsidone derivative from mangrove sediment derived fungus Lasiodiplodia theobromae - Blessing O. Umeokoli; Weaam Ebrahim; Mona El-Neketi; Werner E. G. Müller; Rainer Kalscheuer; Wenhan Lin; Zhen Liu; Peter Proksch (Natural Product Research, 2019)

Myocardial GLP-1 Receptor Activation in the Presence of Glucose: Strong Partners - Ewald Kolesnik; Thomas Krainer; Markus Wallner; Natasa Djalinac; Nicolas Verheyen; Klemens Ablasser; Deborah M. Eaton; Peter P. Rainer; Brigitte Pelzmann; Dirk von Lewinski (International Journal of Peptide Research and Therapeutics, 2019)

Stable nuclear transformation of rhodophyte species Porphyridium purpureum: advanced molecular tools and an optimized method - Binod Prasad; Wolfgang Lein; General Thiyam; Christoph Peter Lindenberger; Rainer Buchholz; Nithya Vadakedath (Photosynthesis Research, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

An optimized method and a dominant selectable marker for genetic engineering of an industrially promising microalga—Pavlova lutheri - Binod Prasad; Wolfgang Lein; Christoph Peter Lindenberger; Rainer Buchholz; Nithya Vadakedath (Journal of Applied Phycology, 2019)

Correction to: The proliferation marker pKi-67 becomes masked to MIB-1 staining after expression of its tandem repeats - Mirko H. H. Schmidt; Rainer Broll; Hans-Peter Bruch; Michael Duchrow (Histochemistry and Cell Biology, 2019)

Correction to: Similar spatial patterns of soil quality indicators in three poplar-based silvo-arable alley cropping systems in Germany - René Beuschel; Hans-Peter Piepho; Rainer Georg Joergensen; Christine Wachendorf (Biology and Fertility of Soils, 2019)

Similar spatial patterns of soil quality indicators in three poplar-based silvo-arable alley cropping systems in Germany - René Beuschel; Hans-Peter Piepho; Rainer Georg Joergensen; Christine Wachendorf (Biology and Fertility of Soils, 2019)

Baiting studies on oral vaccination of the greater kudu (Tragelaphus strepsiceros) against rabies - Rainer Hassel; Steffen Ortmann; Peter Clausen; Mark Jago; Floris Bruwer; Pauline Lindeque; Conrad Freuling; Ad Vos; Thomas Müller (European Journal of Wildlife Research, 2018)

Particulate matter flux interception in oceanic mesoscale eddies by the polychaete Poeobius sp. - Svenja Christiansen; Henk‐Jan Hoving; Florian Schütte; Helena Hauss; Johannes Karstensen; Arne Körtzinger; Simon‐Martin Schröder; Lars Stemmann; Bernd Christiansen; Marc Picheral; Peter Brandt; Bruce Robison; et al. (Limnology and Oceanography, 2018)
Gelatinous zooplankton hold key functions in the ocean and have been shown to significantly influence the transport of organic carbon to the deep sea. We discovered a gelatinous, flux‐feeding polychaete of the genus Poeobius in very high abundances in a mesoscale eddy in the tropical Atlantic Ocean, where it co‐occurred with extremely low particle concentrations. Subsequent analysis of an extensive in situ imaging dataset revealed that Poeobius sp. occurred sporadically between 5°S–20°N and 16°W–46°W in the upper 1000 m. Abundances were significantly elevated and the depth distribution compressed in anticyclonic modewater eddies (ACMEs). In two ACMEs, high Poeobius sp. abundances were associated with strongly reduced particle concentrations and fluxes in the layers directly below the polychaete. We discuss possible reasons for the elevated abundances of Poeobius sp. in ACMEs and provide estimations showing that a single zooplankton species can completely intercept the downward particle flux by feeding with their mucous nets, thereby substantially altering the biogeochemical setting within the eddy.

Surface mapping of the Milh Kharwah salt diapir to better understand the subsurface petroleum system in the Sab’atayn Basin, onshore Yemen - Gabor Tari; Leslie Jessen; Patrick Kennelly; Adel Salman; Thomas Rainer; Peter Hagedorn (Arabian Journal of Geosciences, 2018)

Targeted Next-Generation Sequencing Reveals Novel TTN Mutations Causing Recessive Distal Titinopathy - Anni Evilä; Johanna Palmio; Anna Vihola; Marco Savarese; Giorgio Tasca; Sini Penttilä; Sara Lehtinen; Per Harald Jonson; Jan De Bleecker; Peter Rainer; Michaela Auer-Grumbach; Jean Pouget; et al. (Molecular Neurobiology, 2017)

Organic Agriculture 3.0 is innovation with research - Gerold Rahmann; M. Reza Ardakani; Paolo Bàrberi; Herwart Boehm; Stefano Canali; Mahesh Chander; Wahyudi David; Lucas Dengel; Jan Willem Erisman; Ana C. Galvis-Martinez; Ulrich Hamm; Johannes Kahl; et al. (Organic Agriculture, 2017)

Structure, Mineralogy and Geomechanical Properties of Shear Zones of Deep-Seated Rockslides in Metamorphic Rocks (Tyrol, Austria) - Thomas Strauhal; Christian Zangerl; Wolfgang Fellin; Michael Holzmann; Daniela Anna Engl; Rainer Brandner; Peter Tropper; Richard Tessadri (Rock Mechanics and Rock Engineering, 2017)

P2Y2R is a direct target of HIF-1α and mediates secretion-dependent cyst growth of renal cyst-forming epithelial cells - Andre Kraus; Steffen Grampp; Margarete Goppelt-Struebe; Rainer Schreiber; Karl Kunzelmann; Dorien J.M. Peters; Jens Leipziger; Gunnar Schley; Johannes Schödel; Kai-Uwe Eckardt; Bjoern Buchholz (Purinergic Signalling, 2016)

Digital Fluid Technologies for the Steel Industry - Rudolf Scheidl; Bernd Winkler; Helmut Kogler; Peter Ladner; Rainer Haas; Evgeny Lukachev (BHM Berg- und Hüttenmännische Monatshefte, 2016)

Noble gas composition and 40Ar/39Ar age in eclogites from the main hole of the Chinese Continental Scientific Drilling project - Jens Hopp; Winfried H. Schwarz; Mario Trieloff; Hans-Peter Meyer; Michael Hanel; Rainer Altherr (Contributions to Mineralogy and Petrology, 2016)

Weighing the Evidence: A Systematic Review on Long-Term Neurocognitive Effects of Cannabis Use in Abstinent Adolescents and Adults - Florian Ganzer; Sonja Bröning; Stefanie Kraft; Peter-Michael Sack; Rainer Thomasius (Neuropsychology Review, 2016)

High genetic structuring of Tula hantavirus - Sabrina Schmidt; Moritz Saxenhofer; Stephan Drewes; Mathias Schlegel; Konrad M. Wanka; Raphael Frank; Sven Klimpel; Felix von Blanckenhagen; Denny Maaz; Christiane Herden; Jona Freise; Ronny Wolf; et al. (Archives of Virology, 2016)

Three‐dimensional structure and cyanobacterial activity within a desert biological soil crust - Hagai Raanan; Vincent J. M. N. L. Felde; Stephan Peth; Sylvie Drahorad; Danny Ionescu; Gil Eshkol; Haim Treves; Peter Felix‐Henningsen; Simon M. Berkowicz; Nir Keren; Rainer Horn; Martin Hagemann; et al. (Environmental Microbiology, 2016)
Summary Desert biological soil crusts ( BSC s) are formed by adhesion of soil particles to polysaccharides excreted by filamentous cyanobacteria, the pioneers and main producers in this habitat. Biological soil crust destruction is a central factor leading to land degradation and desertification. We study the effect of BSC structure on cyanobacterial activity. Micro‐scale structural analysis using X ‐ray microtomography revealed a vesiculated layer 1.5–2.5 mm beneath the surface in close proximity to the cyanobacterial location. Light profiles showed attenuation with depth of 1%–5% of surface light within 1 mm but also revealed the presence of ‘light pockets’, coinciding with the vesiculated layer, where the irradiance was 10‐fold higher than adjacent crust parts at the same depth. Maximal photosynthetic activity, examined by O 2 concentration profiles, was observed 1 mm beneath the surface and another peak in association with the ‘light pockets’. Thus, photosynthetic activity may not be visible to currently used remote sensing techniques, suggesting that BSC s' contribution to terrestrial productivity is underestimated. Exposure to irradiance higher than 10% full sunlight diminished chlorophyll fluorescence, whereas O 2 evolution and CO 2 uptake rose, indicating that fluorescence did not reflect cyanobacterial photosynthetic activity. Our data also indicate that although resistant to high illumination, the BSC ‐inhabiting cyanobacteria function as ‘low‐light adapted’ organisms.

Glucose promotes secretion-dependent renal cyst growth - Andre Kraus; Gunnar Schley; Karl Kunzelmann; Rainer Schreiber; Dorien J. M. Peters; Ruth Stadler; Kai-Uwe Eckardt; Bjoern Buchholz (Journal of Molecular Medicine, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Oxidatively damaged guanosine in white blood cells and in urine of welders: associations with exposure to welding fumes and body iron stores - Beate Pesch; Anne Lotz; Holger M. Koch; Boleslaw Marczynski; Swaantje Casjens; Heiko U. Käfferlein; Peter Welge; Martin Lehnert; Evelyn Heinze; Rainer Van Gelder; Jens-Uwe Hahn; Thomas Behrens; et al. (Archives of Toxicology, 2015)

Seroprevalence of hepatitis E virus (HEV) in humans living in high pig density areas of Germany - Andi Krumbholz; Sebastian Joel; Paul Dremsek; Anne Neubert; Reimar Johne; Ralf Dürrwald; Mario Walther; Thomas H. Müller; Detlef Kühnel; Jeannette Lange; Peter Wutzler; Andreas Sauerbrei; et al. (Medical Microbiology and Immunology, 2014)

Enhancing the regeneration of compacted forest soils by planting black alder in skid lane tracks - Christine Meyer; Peter Lüscher; Rainer Schulin (European Journal of Forest Research, 2014)

Synthesis and Optical Properties of Various Thienyl Derivatives of Pyrene - Krzysztof R. Idzik; Tobias Licha; Vladimír Lukeš; Peter Rapta; Jaroslaw Frydel; Mario Schaffer; Eric Taeuscher; Rainer Beckert; Lothar Dunsch (Journal of Fluorescence, 2014)

Innovations in studying in vivo cell behavior and pharmacology in complex tissues – microvascular endothelial cells in the spotlight - Elise Langenkamp; Jan A. A. M. Kamps; Michal Mrug; Elisabeth Verpoorte; Yilmaz Niyaz; Peter Horvatovich; Rainer Bischoff; Harry Struijker-Boudier; Grietje Molema (Cell and Tissue Research, 2013)

Pink manganian phengite in a high P/T meta-conglomerate from northern Syros (Cyclades, Greece) - Rainer Altherr; Christian Soder; Sandra Panienka; Daniel Peters; Hans-Peter Meyer (Contributions to Mineralogy and Petrology, 2013)

Non-linear adaptive controllers for an over-actuated pneumatic MR-compatible stepper - Christoph Hollnagel; Heike Vallery; Rainer Schädler; Isaac Gómez-Lor López; Lukas Jaeger; Peter Wolf; Robert Riener; Laura Marchal-Crespo (Medical & Biological Engineering & Computing, 2013)

Multisite rTMS for the Treatment of Chronic Tinnitus: Stimulation of the Cortical Tinnitus Network—A Pilot Study - Astrid Lehner; Martin Schecklmann; Timm B. Poeppl; Peter M. Kreuzer; Veronika Vielsmeier; Rainer Rupprecht; Michael Landgrebe; Berthold Langguth (Brain Topography, 2013)

Auditory cortex is implicated in tinnitus distress: a voxel-based morphometry study - Martin Schecklmann; Astrid Lehner; Timm B. Poeppl; Peter M. Kreuzer; Rainer Rupprecht; Julia Rackl; Julia Burger; Elmar Frank; Göran Hajak; Berthold Langguth; Michael Landgrebe (Brain Structure and Function, 2013)

Effect of feed supplements on dry season milk yield and profitability of crossbred cows in Honduras - Christoph Reiber; Michael Peters; Jens Möhring; Rainer Schultze-Kraft (Tropical Animal Health and Production, 2013)

Li, Be, B concentrations and δ7Li values in plagioclase phenocrysts of dacites from Nea Kameni (Santorini, Greece) - Joan Cabato; Rainer Altherr; Thomas Ludwig; Hans-Peter Meyer (Contributions to Mineralogy and Petrology, 2013)

Anti-Neuropilin-1 (MNRP1685A): Unexpected Pharmacokinetic Differences Across Species, from Preclinical Models to Humans - Yan Xin; Shuang Bai; Lisa A. Damico-Beyer; Denise Jin; Wei-Ching Liang; Yan Wu; Frank-Peter Theil; Amita Joshi; Yanmei Lu; John Lowe; Mauricio Maia; Rainer K. Brachmann; et al. (Pharmaceutical Research, 2012)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Engineering of vascularized adipose constructs - Paul S. Wiggenhauser; Daniel F. Müller; Ferry P. W. Melchels; José T. Egaña; Katharina Storck; Helena Mayer; Peter Leuthner; Daniel Skodacek; Ursula Hopfner; Hans G. Machens; Rainer Staudenmaier; Jan T. Schantz (Cell and Tissue Research, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Transcript signature predicts tissue NK cell content and defines renal cell carcinoma subgroups independent of TNM staging - Judith Eckl; Alexander Buchner; Petra U. Prinz; Rainer Riesenberg; Sabine I. Siegert; Robert Kammerer; Peter J. Nelson; Elfriede Noessner (Journal of Molecular Medicine, 2012)

QTL involved in the partial restoration of male fertility of C-type cytoplasmic male sterility in maize - Susanne Kohls; Peter Stamp; Carsten Knaak; Rainer Messmer (Theoretical and Applied Genetics, 2011)

DNA adducts and strand breaks in workers exposed to vapours and aerosols of bitumen: associations between exposure and effect - Boleslaw Marczynski; Monika Raulf-Heimsoth; Anne Spickenheuer; Beate Pesch; Benjamin Kendzia; Thomas Mensing; Beate Engelhardt; Eun-Hyun Lee; Birgit K. Schindler; Evelyn Heinze; Peter Welge; Rainer Bramer; et al. (Archives of Toxicology, 2011)

Bitumen workers handling mastic versus rolled asphalt in a tunnel: assessment of exposure and biomarkers of irritation and genotoxicity - Monika Raulf-Heimsoth; Boleslaw Marczynski; Anne Spickenheuer; Beate Pesch; Peter Welge; Reinhold Rühl; Rainer Bramer; Benjamin Kendzia; Evelyn Heinze; Jürgen Angerer; Thomas Brüning (Archives of Toxicology, 2011)

Air sampling and determination of vapours and aerosols of bitumen and polycyclic aromatic hydrocarbons in the Human Bitumen Study - Dietmar Breuer; Jens-Uwe Hahn; Dieter Höber; Christoph Emmel; Uwe Musanke; Reinhold Rühl; Anne Spickenheuer; Monika Raulf-Heimsoth; Rainer Bramer; Albrecht Seidel; Bernd Schilling; Evelyn Heinze; et al. (Archives of Toxicology, 2011)

Levels and determinants of exposure to vapours and aerosols of bitumen - Anne Spickenheuer; Reinhold Rühl; Dieter Höber; Monika Raulf-Heimsoth; Boleslaw Marczynski; Peter Welge; Dietmar Breuer; Stefan Gabriel; Uwe Musanke; Peter Rode; Evelyn Heinze; Benjamin Kendzia; et al. (Archives of Toxicology, 2011)

Isolation, characterization, and bioactivity of endophytic fungi of Tylophora indica - Susheel Kumar; Nutan Kaushik; Ruangelie Edrada-Ebel; Rainer Ebel; Peter Proksch (World Journal of Microbiology and Biotechnology, 2011)

Determination of critical soil water content and matric potential for wind erosion - Kristine Bolte; Peter Hartmann; Heiner Fleige; Rainer Horn (Journal of Soils and Sediments, 2011)

Temperature Control on Soluble Reactive Phosphorus in the Lower Mississippi River? - Shuiwang Duan; Rainer Amon; Thomas S. Bianchi; Peter H. Santschi (Estuaries and Coasts, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Redistribution of HFSE elements during rutile replacement by titanite - Friedrich Lucassen; Peter Dulski; Rainer Abart; Gerhard Franz; Dieter Rhede; Rolf L. Romer (Contributions to Mineralogy and Petrology, 2010)

Capability of a XRF Method for Monitoring the Content of the Macronutrients Mg, P, S, K and Ca in Agricultural Crops - Peter Morgenstern; Lutz Brüggemann; Ralph Meissner; Juliane Seeger; Rainer Wennrich (Water, Air, & Soil Pollution, 2010)

Modulating the activity of the channel-forming segment of Vpr protein from HIV-1 - Chin-Pei Chen; Clemens Kremer; Peter Henklein; Ulrich Schubert; Rainer H. A. Fink; Wolfgang B. Fischer (European Biophysics Journal, 2010)

Changes in soil physical properties of forest floor horizons due to long-term deposition of lignite fly ash - Peter Hartmann; Heiner Fleige; Rainer Horn (Journal of Soils and Sediments, 2010)

On the Resolution Capabilities and Limits of Fluorescence Lifetime Correlation Spectroscopy (FLCS) Measurements - Steffen Rüttinger; Peter Kapusta; Matthias Patting; Michael Wahl; Rainer Macdonald (Journal of Fluorescence, 2010)

Mapping of QTLs for lateral and axile root growth of tropical maize - Samuel Trachsel; Rainer Messmer; Peter Stamp; Andreas Hund (Theoretical and Applied Genetics, 2009)

Drought stress and tropical maize: QTL-by-environment interactions and stability of QTLs across environments for yield components and secondary traits - Rainer Messmer; Yvan Fracheboud; Marianne Bänziger; Mateo Vargas; Peter Stamp; Jean-Marcel Ribaut (Theoretical and Applied Genetics, 2009)

US GODAE: Global Ocean Prediction with the HYbrid Coordinate Ocean Model (HYCOM) - Eric Chassignet; Harley Hurlburt; E. Joseph Metzger; Ole Smedstad; James Cummings; George Halliwell; Rainer Bleck; Remy Baraille; Alan Wallcraft; Carlos Lozano; Hendrik Tolman; Ashwanth Srinivasan; et al. (Oceanography, 2009)

Salt stress affects xylem differentiation of grey poplar (Populus × canescens) - María Escalante-Pérez; Silke Lautner; Uwe Nehls; Anita Selle; Markus Teuber; Jörg-Peter Schnitzler; Thomas Teichmann; Payam Fayyaz; Wolfram Hartung; Andrea Polle; Jörg Fromm; Rainer Hedrich; et al. (Planta, 2009)

Rapid Recovery from Eutrophication of a Stratified Lake by Disruption of Internal Nutrient Load - Thomas Mehner; Markus Diekmann; Thomas Gonsiorczyk; Peter Kasprzak; Rainer Koschel; Lothar Krienitz; Marion Rumpf; Michael Schulz; Gerlinde Wauer (Ecosystems, 2008)

Judging Fitness for Purpose of a X-ray Fluorescence Based Method Investigating the Vertical Distribution of Metals and Metalloids in Soil Profiles - Peter Morgenstern; Lutz Brüggemann; Frank Krüger; Anke Hofacker; Rainer Wennrich (Water, Air, & Soil Pollution, 2008)

The 6th World Meeting on Pharmaceutics, Biopharmaceutics and Pharmaceutical Technology (PBP Meeting) April 7–10, 2008, Barcelona, Spain - Peter Kleinebudde; Rainer Alex; Elias Fattal; Achim Göpferich; Jürgen Siepmann (AAPS PharmSciTech, 2008)

Antifouling Activity of Bromotyrosine-Derived Sponge Metabolites and Synthetic Analogues - Sofia Ortlepp; Martin Sjögren; Mia Dahlström; Horst Weber; Rainer Ebel; RuAngelie Edrada; Carsten Thoms; Peter Schupp; Lars Bohlin; Peter Proksch (Marine Biotechnology, 2007)

Variscan amphibolite-facies rocks from the Kurtoğlu metamorphic complex (Gümüşhane area, Eastern Pontides, Turkey) - Gültekin Topuz; Rainer Altherr; Winfried H. Schwarz; Abdurrahman Dokuz; Hans-Peter Meyer (International Journal of Earth Sciences, 2007)

Mobilization of Antimony and Arsenic in Soil and Sediment Samples – Evaluation of Different Leaching Procedures - Karsten Müller; Birgit Daus; Peter Morgenstern; Rainer Wennrich (Water, Air, & Soil Pollution, 2007)

Description of the first HLA–DRB1 null allele - Britta Eiz-Vesper; Rainer Blasczyk; Peter A. Horn (Immunogenetics, 2007)

In planta AKT2 subunits constitute a pH- and Ca2+-sensitive inward rectifying K+ channel - Andreas Latz; Natalya Ivashikina; Susanne Fischer; Peter Ache; Toshio Sano; Dirk Becker; Rosalia Deeken; Rainer Hedrich (Planta, 2007)

Aberrant expression of HLA-B*3565Q is associated with a disrupted disulfide bond - Holger-Andreas Elsner; Peter A. Horn; Constanze Schoenemann; Wolfgang W. Altermann; Rainer Blasczyk (Immunogenetics, 2006)

Molecular characterization of a collection of the tropical multipurpose shrub legume Flemingia macrophylla - Meike S. Andersson; Michael Peters; Rainer Schultze-Kraft; Gerardo Gallego; Myriam C. Duque (Agroforestry Systems, 2006)

Time course of hypothalamic-pituitary-adrenocortical axis activity during treatment with reboxetine and mirtazapine in depressed patients - Cornelius Schüle; Thomas C. Baghai; Daniela Eser; Peter Zwanzger; Martina Jordan; Renate Buechs; Rainer Rupprecht (Psychopharmacology, 2006)

Neuropsychopharmacological properties of neuroactive steroids in depression and anxiety disorders - Daniela Eser; Cornelius Schüle; Elena Romeo; Thomas C. Baghai; Flavia di Michele; Augusto Pasini; Peter Zwanzger; Frank Padberg; Rainer Rupprecht (Psychopharmacology, 2006)

Safety Evaluation for a Biodiesel Process Using Prion-Contaminated Animal Fat as a Source (6 pp) - Björn Seidel; Martin Alm; Rainer Peters; Werner Kördel; Andreas Schäffer (Environmental Science and Pollution Research, 2006)

Activated Chemical Defense in Aplysina Sponges Revisited - Carsten Thoms; Rainer Ebel; Peter Proksch (Journal of Chemical Ecology, 2006)

Polar-localised poplar K+ channel capable of controlling electrical properties of wood-forming cells - Matthias Arend; Andrea Stinzing; Christa Wind; Katharina Langer; Andreas Latz; Peter Ache; Jörg Fromm; Rainer Hedrich (Planta, 2005)

Differential expression of K+ channels between guard cells and subsidiary cells within the maize stomatal complex - Kai Büchsenschütz; Irene Marten; Dirk Becker; Katrin Philippar; Peter Ache; Rainer Hedrich (Planta, 2005)

Association of a functional BDNF polymorphism and anxiety-related personality traits - Undine E. Lang; Rainer Hellweg; Peter Kalus; Malek Bajbouj; Kirsten P. Lenzen; Thomas Sander; Dieter Kunz; Jürgen Gallinat (Psychopharmacology, 2005)

Phylogeographical footprints of the Strait of Gibraltar and Quaternary climatic fluctuations in the western Mediterranean: a case study with the greater white‐toothed shrew, Crocidura russula (Mammalia: Soricidae) - JEAN‐FRANÇOIS COSSON; RAINER HUTTERER; ROLAND LIBOIS; MAURIZIO SARÀ; PIERRE TABERLET; PETER VOGEL (Molecular Ecology, 2005)
We used mitochondrial cyt b sequences to investigate the phylogenetic relationships of Crocidura russula ( sensu lato ) populations across the Strait of Gibraltar, western Europe, Maghreb, and the Mediterranean and Atlantic islands. This revealed very low genetic divergence between European and Moroccan populations. The application of a molecular clock previously calibrated for shrews suggested that the separation of European from Moroccan lineages occurred less than 60 000 bp , which is at least 5 million years (Myr) after the reopening of the Strait of Gibraltar. This means that an overwater dispersal event was responsible for the observed phylogeographical structure. In contrast, genetic analyses revealed that Moroccan populations were highly distinct from Tunisian ones. According to the molecular clock, these populations separated about 2.2 million years ago (Ma), a time marked by sharp alternations of dry and humid climates in the Maghreb. The populations of the Mediterranean islands Ibiza, Pantelleria, and Sardinia were founded from Tunisian populations by overwater dispersal. In conclusion, overwater dispersal across the Strait of Gibraltar, probably assisted by humans, is possible for small terrestrial vertebrates. Moreover, as in Europe, Quaternary climatic fluctuations had a major effect on the phylogeographical structure of the Maghreb biota.

The Effect of Inoculation Treatment and Long-term Application of Moisture on Fusarium Head Blight Symptoms and Deoxynivalenol Contamination in Wheat Grains - Marc Lemmens; Hermann Buerstmayr; Rudolf Krska; Rainer Schuhmacher; Heinrich Grausgruber; Peter Ruckenbauer (European Journal of Plant Pathology, 2004)

Quantitative measurement of depolarization-induced anandamide release in human and rat neocortex - Marc Steffens; Thomas J. Feuerstein; Vera van Velthoven; Peter Schnierle; Rainer Knörle (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Time-Resolved Fluorescence Anisotropy Measurements Made Simple - Peter Kapusta; Rainer Erdmann; Uwe Ortmann; Michael Wahl (Journal of Fluorescence, 2003)

The proliferation marker pKi-67 becomes masked to MIB-1 staining after expression of its tandem repeats - Mirko H. Schmidt; Rainer Broll; Hans-Peter Bruch; Michael Duchrow (Histochemistry and Cell Biology, 2002)

Molecular structures and associations of humic substances in the terrestrial environment - André J. Simpson; William L. Kingery; Michael H. Hayes; Manfred Spraul; Eberhard Humpfer; Peter Dvortsak; Rainer Kerssebaum; Markus Godejohann; Martin Hofmann (The Science of Nature, 2002)

Prevention of hand dermatitis in bakers' apprentices: different efficacy of skin protection measures and UVB hardening - Andrea Bauer; Daniela Kelterer; Reinhard Bartsch; Anja Schlegel; James Pearson; Martina Stadeler; Peter Kleesz; Romano Grieshaber; Rainer Schiele; Peter Elsner; Hywel Williams (International Archives of Occupational and Environmental Health, 2002)

Uteroglobin promoter-targeted c-MYC expression in transgenic mice cause hyperplasia of Clara cells and malignant transformation of T-lymphoblasts and tubular epithelial cells - Anke Geick; Peter Redecker; Anja Ehrhardt; Rainer Klocke; Dieter Paul; Roman Halter (Transgenic Research, 2001)

Bulk Chemistry Analysis of Sediments from Acid Mine Lakes by Means of Wavelength Dispersive X-ray Fluorescence - Peter Morgenstern; Kurt Friese; Katrin Wendt-Potthoff; Rainer Wennrich (Mine Water and the Environment, 2001)

The plasminogen activator inhibitor 1 4G/5G polymorphism is not associated with longevity: a study in octogenarians - Katja Lottermoser; Rainer Düsing; Peter Ervens; Brigitte Koch; Thomas Brüning; Agapios Sachinidis; Hans Vetter; Yon Ko (Journal of Molecular Medicine, 2001)

In vitro and in vivo uroselectivity of B8805-033, an antagonist with high affinity at prostatic α 1A - vs. α 1B - and α 1D -adrenoceptors - Manfrid Eltze; Rainer Boer; Martin Michel; Peter Hein; Rodolfo Testa; Wolf-Rüdiger Ulrich; Norbert Kolassa; Karl Sanders (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Linkages among the bioreactivity, chemical composition, and diagenetic state of marine dissolved organic matter - Rainer M. W. Amon; Hans-Peter Fitznar; Ronald Benner (Limnology and Oceanography, 2001)
Bacterial growth and the chemical composition of dissolved organic matter (DOM) were followed during a 10ߚd decomposition experiment with fresh, algalߚ;derived DOM from an Arctic ice floe. During the experiment ~30% of the dissolved organic carbon (DOC) was used by bacteria, indicating the highly reactive nature of this fresh DOM. Over half of the DOC consumption was accounted for as losses of combined neutral sugars and amino acids. The initial composition of the DOM was characterized by high neutral sugar (14% DOC) and amino acid (7.4% DOC) yields and the dominance of glucose (~75 mol%) and glutamic acid (~25 mol%). During microbial degߚradation the neutral sugar and amino acid yields decreased, and the molecular composition of the DOM became more uniform. The relatively constant abundance of D amino acids and the dramatic changes in the neutral sugar and amino acid compositions indicated that bacteria were important in shaping the chemical composition of marine DOM by selectively removing bioreactive components and by leaving behind biorefractory components. Based on principal component analysis and other parameters, neutral sugars and amino acids were found to be excellent indicators of the diagenetic state and bioavailability of marine DOM.

The GAA repeat expansion in intron 1 of the frataxin gene is related to the severity of cardiac manifestation in patients with Friedreich's ataxia - Nana Bit-Avragim; Andreas Perrot; Ludger Schöls; Cornelia Hardt; Friedmar R. Kreuz; Christine Zühlke; Stefanie Bubel; Franco Laccone; Hans-Peter Vogel; Rainer Dietz; Karl Josef Osterziel (Journal of Molecular Medicine, 2001)

An amicyanin C-terminal loop mutant where the active-site histidine donor cannot be protonated - Rainer Remenyi; Lars J.C. Jeuken; Peter Comba; Gerard W. Canters (JBIC Journal of Biological Inorganic Chemistry, 2001)

20th International Symposium on Halogenated Environmental Organic Pollutants & POPS - Heidi Fiedler; Peter Fürst; Rainer Malisch; Olaf Päpke; Dieter Schrenk (Environmental Science and Pollution Research, 2000)

pH regulation in isolated in vitro perfused rat colonic crypts - Peter Hasselblatt; Richard Warth; Annette Schulz-Baldes; Rainer Greger; Markus Bleich (Pflügers Archiv - European Journal of Physiology, 2000)

Expression and function of β-glucuronidase in pancreatic cancer: potential role in drug targeting - Bernhard Sperker; Ulrike Werner; Thomas E. Mürdter; Ceren Tekkaya; Peter Fritz; Rainer Wacke; Ulrich Adam; Manfred Gerken; Bernd Drewelow; Heyo K. Kroemer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Gabapentin-lactam (8-aza-spiro[5,4]decan-9-on; GBP-L) inhibits oxygen glucose deprivation-induced [ 3 H]glutamate release and is a neuroprotective agent in a model of acute retinal ischemia - Thomas Jehle; Wolf A. Lagrèze; Eckard Blauth; Rainer Knörle; Peter Schnierle; Carl Hermann Lücking; Thomas J. Feuerstein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Lung cancer mortality among European rock/slag wool workers: exposure-response analysis - Dario Consonni; Paolo Boffetta; Gilles Ferro; Rodolfo Saracci; Aage Andersen; Jenny Chang-Claude; John W. Cherrie; Rainer Frentzel-Beyme; Johnni Hansen; Jørgen Olsen; Nils Plato; Peter Westerholm (Cancer Causes & Control, 1998)

Cation sensitivity and kinetics of guard-cell potassium channels differ among species - Petra Dietrich; Ingo Dreyer; Peter Wiesner; Rainer Hedrich (Planta, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Wound Activation of Protoxins in Marine Sponge Aplysina aerophoba - Rainer Ebel; Marko Brenzinger; Arno Kunze; Hans J. Gross; Peter Proksch (Journal of Chemical Ecology, 1997)

Carrier-mediated acetate transport in Acetobacterium woodii - Rainer Boenigk; Peter Drre; Gerhard Gottschalk (Archives of Microbiology, 1989)